Prediction of stroking characteristics of elite rowers from anthropometric variables - Dimakopoulou, E.; Blazevich, J. A.; Kaloupsis, S.; Diafas, V.; Bachev, V. (Serbian Journal of Sports Sciences, 2007)
A theoretical model was developed to identify anthropometric variables relevant to stroke rate and length selection in rowing at various intensities. Lengths of body segments were measured on eight members of a juniors` club team using standardized anthropometric procedures. Motion picture films were taken of the subjects on rowing ergometer performing different intensities tests and were analyzed to determine the stroke length (SL) and stroke rate (SR). Correlation was used to determine the relationships between anthropometric variables. MANOVA was performed to determine the differences between SL and SR at various rowing intensities. Regression (stepwise) analysis was used to predict the stroke lengths and rates at different power outputs from anthropometric data. The prediction model revealed that arm length, thigh length and sitting height are the best predictors of SL and SR at all power outputs. These results suggested that self selected SL and SR is very much a function of the physique of the athlete. Coaches should possibly put athletes of the same anthropometric characteristics in the same boat in order to better synchronize rowing strokes in a boat.